Non-Cash Transaction Policy: The Steps for Cashless Management in Central Java Province - Setiawan, Zeffri; Rosidi; Purwanti, Lilik (The International Journal of Accounting and Business Society, 2022)
Purpose - This study aims to understand the implementation steps of the non-cash transaction policy in the Central Java Provincial Government, with Edward III's (1980) "Policy Implementation Theory" as a tool for analyzing the supporting and inhibiting factors of implementation. Design/methodology/approach—This research uses a qualitative approach. Data was collected through in-depth interviews and document collection regarding the application of non-cash transactions. The informants in this study involved 2 participants from the Regional Financial and Asset Management Agency of Central Java Province. These participants are policymakers and technical implementers who apply non-cash transactions to the research object. Findings - Result Research shows that implementing the non-cash transaction policy has been going well from the perspective of the executor's understanding of non-cash management. The Central Java Provincial Government takes steps in policy implementation: preparation, implementation, and control. Supporting factors in implementation come from communication and financial resources. Meanwhile, human resources, physical resources, disposition and bureaucracy need to be evaluated because they can potentially hinder implementation in the Central Java Provincial Government. Practical implications—The implementation of the non-cash transaction policy found supporting factors and obstacles. This is useful in improving the quality of local government financial management so that implementation is not limited to fulfilling obligations but also has uses. Originality/value - Implementing non-cash transactions is necessary for Regional Governments because it brings many benefits in the context of realizing good governance. This study seeks to analyze the application of non-cash transactions and identify the causes of the low application of non-cash transactions. This study reveals the facts related to implementing the non-cash transaction policy so that it can provide input to the government in implementing regional financial management. Keywords- Cashless, Public Policy; Financial Administration; Edwards III Theory Paper type- Case study